About sign language translator application - Navasardyan, Armine; Knkoyan, Gohar
The Sign language translator is a trilingual mobile app for translating speech into international sign language. The developed mobile application is designed for the people who have hearing problems and use sign language. It converts imported audio information into texts and simultaneously translates it into the international sign language. The application works for Armenian, Russian and English languages. It has an admin module that allows you to add new words, edit or remove them. It has simple three-language operating interfaces. The application works on both Windows and Android operating systems. It does not require additional resources or investments. It can be useful for inclusive societies and education.
Keywords: International sign language